Review of Particle Physics - Caso, C; Conforto, G; Gurtu, A; Aguilar-Benitez, M; Amsler, C; Barnett, R; Burchat, P; Carone, C; Dahl, O; Doser, M; Eidelman, S; Feng, J; et al. (1998)
This biennial Review summarizes much of Particle Physics. Using data from previous editions, plus 2000 new measurements from 610 papers, we list, evaluate, and average measured properties of gauge bosons, leptons, quarks, mesons, and baryons. We also summarize searches for hypothetical particles such as Higgs bosons, heavy neutrinos, and supersymmetric particles. All the particle properties and search limits are listed in Summary Tables. We also give numerous tables, figures, formulae, and reviews of topics such as the Standard Model, particle detectors, probability, and statistics. A booklet is available containing the Summary Tables and abbreviated versions of some of the other sections of this full Review. © 2000 Regents of the University of California.